PENDAMPINGAN PEMANFAATAN TEKNOLOGI INFORMASI UNTUK PERLOMBAAN BERBASIS Cc5+ OSTRANAS III â€œPERWUJUDAN NILAI - NILAI Cc5+â€ - Jevanda, Klaudius; Nurmansyah, Wawan; Akbar, Reza (Universitas Negeri Surabaya, 2019)
Community Service Activities aims to provide assistance by utilizing IT in the realization of Cc5 + values for students of SMP St. Yoseph Lahat. The specific target expected from this activity is the increased ability of junior high school students. Yoseph Lahat in designing and creating interactive IT-based presentation materials to prepare the competition OSTARNAS III. The software used is MS Power Point. Methods of implementation undertaken starting from the determination of partners, justification partner issues, procedures undertaken, work plans, and the expec ted output in the mentoring activities. Outcome of the implementation of this activity is expected: 1)students make presentations about interactive Cc5 + values using IT-based technology, 2) students understand the use of technology in making presentation materials about Cc5 + values as a support for the preparation process of the OSTARNAS III contest, and 3) the students mastered the presentation material on Cc5 + values with the best preparation for the competition OSTARNAS III. The results of the questionnaire stated that the OSTARNAS III advisory activities agreed / benefited by 46.67% and strongly agreed / beneficial to Junior High School students. Yosef Lahat equal to 53.33%